Cover Picture: Divergent Reactivity of In Situ Generated Metal Azides: Reaction with N, N‐Bis(oxy)enamines as a Case Study (Chem. Eur. J. 19/2017). Issue 19 (16th February 2017) - Zhmurov, Petr A.; Khoroshutina, Yulia A.; Novikov, Roman A.; Golovanov, Ivan S.; Sukhorukov, Alexey Yu.; Ioffe, Sema L.
Abstract : In the "chemical billiard" reaction shown on the front cover, a counter ion directs the attack of the azide anion to one or another electrophilic center of the organic substrate. Covalently bonded metal azides transfer N3 − to the β‐carbon atom through a Lewis‐acid‐promoted SN ' process, while ionic azides react through SN 2 attack on the silicon. These two pathways lead to entirely different products. More information can be found in the Full Paper by A. Yu. Sukhorukov et al. onpage 4570 ff.